Emerging opportunities for the treatment of metabolic diseases: Glucagon-like peptide-1 based multi-agonists. (15th December 2015) - Finan, Brian; Clemmensen, Christoffer; Müller, Timo D.
Abstract: Obesity is a pathogenic gateway to the metabolic syndrome and the complications thereof, thus interventions aimed at preventing or reversing the metabolic derangements underlying obesity hold great therapeutic promise. However, the complexity of energy balance regulation, combined with the heterologous pathophysiology of human obesity, renders effective medicinal intervention very difficult. Indeed, the search for the silver bullet in anti-obesity medicines has been laden with drugs of underwhelming efficacy and unacceptable side effects. This can partly be the consequence that many of these drug interventions have been historically directed at single molecular targets. New multi-molecular combination therapies have shown promising clinical outcomes in terms of weight loss, yet multi-functional single molecules may offer even more advantages than adjunctive co-treatments. Single molecules with integrated activities derived from multiple hormones involved in the physiological control of metabolism have emerged as one of the more promising candidates for reversing obesity. The inclusion of glucagon-like peptide-1 (GLP-1) as one of the constituents is a unifying factor amongst the majority of these unimolecular multi-agonists. The scope of this review is to summarize the current preclinical and clinical landscape of GLP-1-based therapies, focusing on combinatorial therapies with a particular emphasis on single molecule compounds displaying multi-agonist properties. Highlights: Summary of GLP-1R agonists currently approved or in clinical development for T2D. Snapshot of selected GLP-1 based combination therapies for obesity. Overview of single molecule GLP-1 based multi-agonists.